The evaluation of the educational system in the region of Murcia. Actions of the inspection of education - Esteban Luis, María del Rocío; López García, M.ª Teresa (Avances en Supervisión Educativa, 2023)
Assessment is an essential factor to improve and increase the transparency of the education system. In this article, we take a look at different actions in which we can observe how the Education Inspectorate of the Autonomous Community of Murcia deals with educational assessment. On the one hand, we describe the involvement of the Education Inspectorate in external assessments and in the improvement plans drawn up following the analysis of the results of these assessments. On the other hand, we explain the collaboration of the Inspection of Education in the implementation of a culture of continuous improvement towards excellence at schools through the Common Assessment Framework (CAF Education) model of excellence. To conclude, this article details the involvement of the Education Inspectorate in the assessment of one of the fundamental elements of the vocational education and training system: the assessment of learning outcomes in distance education programs.
Keywords: Region of Murcia; External Evaluation; Inspection of Education; plans to improve; learning outcomes; vocational training